The consequences of the single supervisory mechanism for Europe's macro-prudential policy framework - André Sapir; Martin F. Hellwig; Marco Pagano; Viral V. Acharya; Leszek Balcerowicz; Arnoud Boot; Markus K. Brunnermeier; Claudia Buch; Ieke van den Burg; Charles Calomiris; Daniel Gros; Dario Focarelli; et al. (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2013)
The European macro-prudential policy framework operates at two levels. First, the ESRB has a legal responsibility for macro-prudential oversight in the EU. Second, various national and EU authorities have responsibility for the implementation of macro-prudential policy. The creation of a European banking union is an important innovation within this two-level structure. In response to this innovation, this paper makes two key points. First, the ECB should be in charge of macro-prudential policies conferred by the Capital Requirements Regulation and Directive. Within the ECB, macro-prudential decisions should be taken entirely by the Governing Council, while micro-prudential decisions should be prepared by the Supervisory Board. Second, the ESRB remains the only EU-wide body in charge of macro-prudential supervision, responsible for all financial activities. The ESRB's effectiveness could be strengthened by creating a post of Managing Director, who would carry out the policy determined by the General Board and would be responsible to the General Board for the management of the ESRB.
Keywords: G28; 330; macroprudential regulation; market integration